Amphiphilic Block Copolymer Vesicles for Active Wound Dressings: Synthesis of Model Systems and Studies of Encapsulation and Release. Issue 1 (12th July 2013) - Haas, Simon; Chen, Yizhou; Fuchs, Christian; Handschuh, Stephan; Steuber, Marc; Schönherr, Holger; Kovačević, Vera
Summary Polystyrene‐block‐poly(acrylic acid) (PS‐b‐PAA) diblock copolymers were synthesized via atom transfer radical polymerization (ATRP). Self‐assembly of these block copolymers into polymeric vesicles, so‐called polymersomes, was performed by addition of water to a solution of the block copolymers in tetrahydrofuran (THF). Various antimicrobial compounds and dyes were incorporated in the polymersomes and in addition to the corresponding size distributions, as determined by dynamic light scattering (DLS), the maximum attainable loading concentrations were determined. Using the release of incorporated calcein, which is a pH responsive dye, the principle of a light up probe approach for advanced in situ diagnostics was demonstrated. The release from PS‐b‐PAA vesicles via a vesicle‐to‐micelle transition was triggered by heating a vesicle suspension after addition of the plasticizer THF to 50 °C. Furthermore, a biocompatible and degradable block copolymer system, which contains degradable ester bonds in the main chain, was synthesized and investigated. In particular, poly(ethylene glycol)‐block‐polycaprolactone (PEG‐b‐PCL) copolymers were synthesized via ring‐opening polymerization (ROP). These copolymers were shown to form polymersomes as well and represent a promising family of degradable amphiphilic block copolymers for active wound dressings and related applications.